Screening and Management of Colon Polyp as Colorectal Cancer Prevention - Gratcia Ayundini; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2016)
Colon polyp is a term used for abnormality from bulging tissue above surrounding colonic mucosal layer. Adenoma polyp was the commonly found polyp that progress to colorectal cancer. Most of those patients was asymptomatic. Undetected and unmanaged polyp was a risk factors of colorectal cancer event.